Investigation on the effect of stimulated Raman scattering in remotely‐pumped L‐band erbium‐doped fiber amplifier - Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir; Mokhtar, Makhfudzah; Abas, Ahmad Fauzi; Md. Yusoff, Nelidya (WILEY‐VCH Verlag GmbH & Co. KGaA, 2009)
The effect of stimulated Raman scattering (SRS) in remote pumping scheme for L‐band erbium‐doped fiber amplifier (EDFA) was studied in this experiment. Observation was done on the gain and noise figure performance as well as the Raman distributed gains of the remotely‐pumped L‐band erbium‐doped fiber amplifier with the existence of SRS. The utilization of SRS effect as a secondary pump for L‐band EDFA demonstrated improvements over single pump EDFA at low pump power due to the additional power from the generated C‐band stimulated Raman scattering or SRS. Nevertheless, the augmentation of the Cband SRS power as the pump was increased, caused gain competition with the L‐band signal which ultimately affected the performance of the L‐band EDFA. The Raman distributed gain was also influenced by the C‐band SRS existence, which saw declining L‐band gains as the C‐band SRS rose and then improved values once the C‐band SRS is saturated.